2014
DOI: 10.1371/journal.pone.0096119
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Nasal Carriage of Staphylococcus aureus in an Urban and a Rural Community in Ghana

Abstract: The epidemiology of Staphylococcus aureus in the community in Ghana was never investigated prior to this study. The aims of the study were: i) to assess prevalence of nasal S. aureus carriage in Ghanaian people living in an urban and a rural area, and ii) to identify phenotypic and genotypic traits of strains isolated from the two communities. Nasal swabs were collected from healthy individuals living in an urban community situated in the suburb of the capital city, Accra (n = 353) and in a rural community sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
55
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 43 publications
21
55
4
Order By: Relevance
“…Table 2 shows the molecular characteristics of all S. aureus isolates in the study. PVL-postive isolates (3/10, 30%) belonged to CC15 (n = 1) and CC152 (n=2), similar to the observation in earlier studies in Ghana [8,9,13].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Table 2 shows the molecular characteristics of all S. aureus isolates in the study. PVL-postive isolates (3/10, 30%) belonged to CC15 (n = 1) and CC152 (n=2), similar to the observation in earlier studies in Ghana [8,9,13].…”
Section: Resultssupporting
confidence: 88%
“…The finding of spa type t084 in multiple patients was anticipated as this lineage was common in earlier hospital and community studies in Ghana [8,9,13]. Surprisingly, spa type t355, the frequent clone detected among clinical and non clinical isolates in recent studies in Ghana [8,9,13] was not found among this group of patients suggesting differences in S. aureus clone distribution with patient groups in this country. Table 2 shows the molecular characteristics of all S. aureus isolates in the study.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Resistances to ampicillin and tetracycline have been reported worldwide [5], including referral hospitals in Tanzania [31,32] and community settings in other African countries such as Ghana [33]. Resistance to gentamicin was reported in 41.5% of human clinical isolates derived from a hospital in Tanzania [34] but it was low among human and animal isolates investigated by our study.…”
Section: Discussionmentioning
confidence: 61%
“…It was determined that the human strains originated from a bovine to human host jump believed to have occurred approximately 40 years ago and subsequently acquired methicillin resistance [81]. MSSA CC97 strains are still circulating in humans [82,83].…”
Section: Cc97mentioning
confidence: 99%